Identification of biomarker candidates for filarial parasite infections by analysis of extracellular vesicles - Yates, Devyn; Di Maggio, Lucia S.; Rosa, Bruce A.; Sprung, Robert W.; Erdmann-Gilmore, Petra; Townsend, R. Reid; Budge, Philip J.; Kamgno, Joseph; Mitreva, Makedonka; Weil, Gary J.; Fischer, Peter U. (Frontiers in Parasitology, 2023)
Background: Improved diagnostic tools are needed for detecting active filarial infections in humans. Tests are available that detect adult W. bancrofti circulating filarial antigen, but there are no sensitive and specific biomarker tests for brugian filariasis or loiasis. Here we explored whether extracellular vesicles released by filarial parasites contain diagnostic biomarker candidates. Methods: Vesicles were isolated using VN96-affinity purification from supernatants of short-term in vitro cultured B. malayi microfilariae (Mf) and analyzed by mass spectrometry (Bruker timsTOF). Parasite-specific proteins were identified by bioinformatic analysis and a protein was called present if supported by ≥ 2 spectra. After validation with cultures parasites, this approach was then used to analyze vesicles isolated from plasma of animals infected with B. malayi and from humans with heavy Loa loa infections. Results: Vesicles from Mf cultures contained more than 300 B. malayi proteins with high consistency across biological replicates. These included the known Mf excretory antigen BmR1 (AF225296). Over 150 B. malayi proteins were detected in vesicles isolated from plasma samples from two infected animals. Vesicles isolated from plasma from 10 persons with high L. loa Mf densities contained consistently 21 proteins, 9 of them were supported by at least 5 unique peptides and 7 with spectral counts above 10. The protein EN70_10600 (an orthologue of the B. malayi antigen BmR1, GenBank AF225296) was detected in all 10 samples with a total count of 91 spectra and a paralogue (EN70_10598) was detected in 6 samples with a total of 44 spectra. Discussion: Extracellular vesicles released by filarial parasites in vitro and in vivo contain parasite proteins which can be reliably detected by mass spectrometry. This research provides the foundation to develop antigen detection assays to improve diagnosis of active filarial infections in humans.